Fluid distribution optimization in porous media using leaf venation patterns - Oliveira, Caio Martins Ramos de (2017)
Several examples of nearly optimal transport networks can be found in nature. These networks effectively distribute and drain fluids throughout a medium. Evidence suggests that blood vessels of the circulatory system, airways in the lungs and veins of leaf venations are examples of networks that have evolved to become effective in their tasks while simultaneously being energy efficient. Hence, it does not come as a surprise that recent performance improvements of modern power generating devices occur due to the use of nature-inspired channel architectures. Guided by this observations, in this work, we investigate the application of visually realistic computer-generated leaf venation patterns to a type of photovoltaic device. We solve the flow through the device problem using Computational Fluid Dynamics (CFD) tools. Moreover, we attempt to develop experimentals models. Ultimately, we seek to single out the network properties that affect their performance.